A novel Atg5-shRNA mouse model enables temporal control of Autophagy in vivo. Issue 7 (3rd July 2018) - Cassidy, Liam D.; Young, Andrew RJ.; Pérez-Mancera, Pedro A.; Nimmervoll, Birgit; Jaulim, Adil; Chen, Hung-Chang; McIntyre, Dominick J. O.; Brais, Rebecca; Ricketts, Thomas; Pacey, Simon; De La Roche, Maike; Gilbertson, Richard J.; et al.
ABSTRACT: Macroautophagy/autophagy is an evolutionarily conserved catabolic pathway whose modulation has been linked to diverse disease states, including age-associated disorders. Conventional and conditional whole-body knockout mouse models of key autophagy genes display perinatal death and lethal neurotoxicity, respectively, limiting their applications for in vivo studies. Here, we have developed an inducible shRNA mouse model targeting Atg5, allowing us to dynamically inhibit autophagy in vivo, termed ATG5i mice. The lack of brain-associated shRNA expression in this model circumvents the lethal phenotypes associated with complete autophagy knockouts. We show that ATG5i mice recapitulate many of the previously described phenotypes of tissue-specific knockouts. While restoration of autophagy in the liver rescues hepatomegaly and other pathologies associated with autophagy deficiency, this coincides with the development of hepatic fibrosis. These results highlight the need to consider the potential side effects of systemic anti-autophagy therapies.